China's soft power diplomacy in South Asia : myth or reality? - Jain, B. M. (Lexington Books, 2017)
This book examines the Chinese version of soft power and explores its myriad implications for India and all of South Asia. It traces the origin of China's engagement with South Asian states from historical, political, economic, and security perspectives in order to better understand the dynamics of its South Asia policy.